2016
DOI: 10.1128/iai.00635-16
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal Outer Membrane Vesicle Composition-Dependent Activation of the Innate Immune Response

Abstract: cMeningococcal outer membrane vesicles (OMVs) have been extensively investigated and successfully implemented as vaccines. They contain pathogen-associated molecular patterns, including lipopolysaccharide (LPS), capable of triggering innate immunity. However, Neisseria meningitidis contains an extremely potent hexa-acylated LPS, leading to adverse effects when its OMVs are applied as vaccines. To create safe OMV vaccines, detergent treatment is generally used to reduce the LPS content. While effective, this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Compared to traditional method like chemical modification based on the structure of LPS or LTA, the biosafety of OMV will be improved after the rational genetic manipulation, which will further increase the therapeutic potential of OMV . Some studies have shown that OMVs from genetically engineered bacteria such as E. coli, Neisseria meningitidis and S. aureus show low toxicity and can effectively induce antibody-mediated immunity or innate immune response (Fantappie et al 2014;Zariri et al 2016).…”
Section: Genetically Engineered Omvs For Vaccine Developmentmentioning
confidence: 99%
“…Compared to traditional method like chemical modification based on the structure of LPS or LTA, the biosafety of OMV will be improved after the rational genetic manipulation, which will further increase the therapeutic potential of OMV . Some studies have shown that OMVs from genetically engineered bacteria such as E. coli, Neisseria meningitidis and S. aureus show low toxicity and can effectively induce antibody-mediated immunity or innate immune response (Fantappie et al 2014;Zariri et al 2016).…”
Section: Genetically Engineered Omvs For Vaccine Developmentmentioning
confidence: 99%
“…Low-LPS OMVs were prepared according to previous reports (Claassen et al, 1996;Zariri et al, 2016) with minor modifications. Briefly, the bacterial cultures were pelleted as described above and resuspended in 0.1 M Tris-10 mM EDTA buffer.…”
Section: Bacterial Outer Membrane Vesicles Regulate Intestinal Ugt1a1mentioning
confidence: 99%
“…Clostridium difficile, Porphyromonas gingivalis, Neisseria meningitidis and Staphylococcus aureus have displayed immunological outcomes, including those mediated by TLR2 and TLR4 [1][2][3][4][5]. Moreover, in vitro transcriptome analysis suggested that LPS structural changes can be used to alter immunological outcome [6].…”
Section: Mvs Isolated From Diverse Species Such As Legionella Pneumomentioning
confidence: 99%